Chromatin in 3D: progress and prospects for plants - Liu, Chang (Genome Biol, 2015)
Methods that use high-throughput sequencing have begun to reveal features of the three-dimensional structure of genomes at a resolution that goes far beyond that of traditional microscopy. Integration of these methods with other molecular tools has advanced our knowledge of both global and local chromatin packing in plants, and has revealed how patterns of chromatin packing correlate with the genomic and epigenomic landscapes. This update reports recent progress made in this area in plants, and suggests new research directions.